Prenatal diagnosis of the recurrent 1q21.1 microdeletions in fetuses with ultrasound anomalies and review of the literature - Liu, Lei; Lei, Tingying; Guo, Fei; Ma, Chunling; Zhen, Li; Zhang, Lina; Li, Dongzhi (Frontiers in Genetics, 2024)
Objective The recurrent 1q21.1 microdeletion syndrome is an autosomal dominant disorder and is characterized by dysmorphic facial features, microcephaly, developmental delay, and congenital defects. However, most studies on the distal deletions in the 1q21.1 region were diagnosed postnatally. This study aimed to provide a better understanding of the ultrasound and molecular findings of fetuses with recurrent 1q21.1 microdeletions in prenatal diagnosis. Methods In this retrospective study, we reported 21 cases with the recurrent 1q21.1 microdeletion syndrome diagnosed at our prenatal diagnostic center from January 2016 to January 2023. The clinical data were reviewed for these cases, including the maternal demographics, indications for invasive testing, ultrasound findings, CMA results, and pregnancy outcomes. Results In the study, a total of 21 cases with recurrent 1q21.1 microdeletions were diagnosed prenatally by CMA. Fifteen cases were described with ultrasound indications, and the most common findings are as follows: increased nuchal translucency (NT) (26.7%), intrauterine growth retardation (IUGR) (26.7%), congenital heart defects (CHD) (20%), and congenital anomalies of the kidney and urinary tract (CAKUT) (13.3%). All the cases with the distal 1q21.1 deletions contain the common minimal region (located between BP3 and BP4) and eight OMIM genes. Parental studies to determine the inheritance of the deletion were performed for eight cases, and half of the cases were inherited from one of the parents. Pregnancy outcomes were available for nine cases; eight (88.9%) pregnancies were determined to be terminated and one (11.1%) was full-term delivery. Conclusion To our knowledge, this is the largest study to find that fetuses with recurrent 1q21.1 microdeletions were closely associated with increased NT, CHD, IUGR, and CAKUT. In addition, ours is the first study to report that cerebral ventriculomegaly might be associated with recurrent 1q21.1 microdeletions. More comprehensive studies are needed for a better understanding of the prenatal phenotype–genotype relationship of the recurrent 1q21.1 microdeletion syndrome in future.